The Moderating Role of Governance on the Effects of FDI, Trade Openness, Manufacturing, and Labor Force on Economic Growth: Evidence from Dynamic Panel GMM in Middle-Income Asian Countries - Alfadri, Ferri; Pulungan, Ismail; Lubis, Rizki Mulia (Ekonomi Syariah IAIN Kudus, 2026)
This study empirically examines the effects of manufacturing, foreign direct investment (FDI), trade openness, and the labor force on economic growth in middle-income Asian countries during 2004–2024, with governance serving as a moderating variable. Using a dynamic panel Generalized Method of Moments (GMM) approach complemented by Moderated Regression Analysis (MRA), the findings reveal that manufacturing, FDI, and trade openness do not exhibit statistically significant direct effects on economic growth, while labor force growth shows a negative and significant impact, indicating structural inefficiencies and productivity constraints. The results further demonstrate that governance plays a crucial conditioning role in shaping the effectiveness of economic activities, suggesting that economic growth drivers can contribute to growth only when supported by strong institutional frameworks. From an Islamic economics perspective, these findings highlight that economic growth cannot be achieved solely through the expansion of production inputs or capital inflows, but must be embedded within governance structures that uphold justice (‘adl), trust (amanah), and public welfare (maslahah), in line with maqasid al-shariah. The study contributes to the Islamic economics literature by reinterpreting conventional growth determinants through a maqasid-oriented governance framework, emphasizing governance's central role in promoting inclusive and sustainable economic growth in middle-income Asian countries.